Aleukemic Leukemia Cutis Manifesting with Disseminated Nodular Eruptions and a Plaque Preceding Acute Monocytic Leukemia: A Case Report - Ipek Yonal (Case Reports in Oncology, 2011)
Aleukemic leukemia cutis (ALC), a discrete tumor of leukemic cells involving the skin, may be the first manifestation of acute myeloid leukemia, preceding the onset in marrow and blood by months and years. ALC is often difficult to diagnose and is associated with a dismal prognosis. A 63-year-old male presented with nodular swellings on the face, a plaque extending over the right shoulder and multiple enlarged cervical lymph nodes. The skin biopsy of the plaque lesion showed a diffuse neoplastic infiltration extending from the dermis to subcutaneous tissue with diffuse positivity for myeloperoxidase and focal positivity for CD34 on immunohistochemical staining. The diagnosis was leukemia cutis. One month later, acute monocytic leukemia (FAB AML-M5b) was diagnosed. The patient died on the seventh month of diagnosis.